Ego Zoom - Alemán, Álvaro (Ánima, 2021)
The text attempts to link the global exercise of using the digital application Zoom with a new communicative sensitivity. Based on an analysis of the interest placed on attention in the last century and in the present, the document attempts to mark some facets of the encounter in Zoom through examples derived from modern poetry, finally an approach to the Zoom application is tried through the etymological and methodological.